2021
DOI: 10.1016/j.cellsig.2021.110064
|View full text |Cite
|
Sign up to set email alerts
|

TRIM28 regulates SARS-CoV-2 cell entry by targeting ACE2

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the cause of coronavirus disease 2019, it binds to angiotensin-converting enzyme 2 (ACE2) to enter into human cells. The expression level of ACE2 potentially determine the susceptibility and severity of COVID-19, it is thus of importance to understand the regulatory mechanism of ACE2 expression. Tripartite motif containing 28 (TRIM28) is known to be involved in multiple processes including antiviral restriction, endogenous retrovirus latency and i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 51 publications
0
16
1
Order By: Relevance
“…Another pSNV in TRIM28, R472C, occurs upstream of the S473 phosphosite; however, unlike S473L, this substitution does not cause significant motif alterations. A recent study showed that knockdown of TRIM28 activates ACE2 and leads to increased host cell entry of SARS‐CoV‐2 (Wang et al , 2021 ). TRIM28 expression also correlates with interferon levels, being lower in children with severe COVID‐19 disease and multisystem inflammatory syndrome (MIS‐C) compared to uninfected children and those with mild disease (Tovo et al , 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Another pSNV in TRIM28, R472C, occurs upstream of the S473 phosphosite; however, unlike S473L, this substitution does not cause significant motif alterations. A recent study showed that knockdown of TRIM28 activates ACE2 and leads to increased host cell entry of SARS‐CoV‐2 (Wang et al , 2021 ). TRIM28 expression also correlates with interferon levels, being lower in children with severe COVID‐19 disease and multisystem inflammatory syndrome (MIS‐C) compared to uninfected children and those with mild disease (Tovo et al , 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Alveolar epithelial cells are frequently the first type of cell to suffer the damage caused by pathogenic microbial cells, which include not only the inflammatory and target cells but also active inflammatory and effector cells ( 32 , 33 ). The A549 cell line, orignally a lung cancer cell line, is a widely used cell line in research on alveolar epithelial cell biology and its shared characteristics with type II alveolar epithelial cells have been demonstrated in vitro ; the response of this cell line to various interventions is constant and repeatable, so it may be used in the study of relevant interventions ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, Tovo et al conducted a clinical correlation study showing that children infected with SARS-CoV-2 had upregulated levels of KAP1 and SETDB1 along with type 1 interferon-stimulated genes, proposing that KAP1 may play a repressive role in infection (Tovo et al, 2021). In addition to this correlational study, another group found that KAP1 silencing using siRNA led to enhanced expression of ACE2, the SARS-CoV-2 receptor, in cancer cell models and primary human lung epithelial cells (Wang et al, 2021). Despite these two studies, the mechanism of action and whether KAP1 truly plays a repressive role in the SARS-CoV-2 infection remains unclear.…”
Section: Rna Virusesmentioning
confidence: 97%